Laboratory chamber measurements of the longwave extinction spectra and complex refractive indices of African and Asian mineral dusts. Issue 17 (2nd September 2014) - Di Biagio, C.; Formenti, P.; Styler, S. A.; Pangui, E.; Doussin, J.‐F.
Abstract In this study we present the first results from laboratory chamber experiments newly designed to investigate the longwave optical properties of mineral dust. Extinction spectra in the 2–16 µm range have been measured in situ (T = 293 K, RH < 2%) for polydispersed pure dust aerosols generated from natural parent soils from Tunisia, Niger, and the Gobi desert. Data are used in combination with particle size distributions to estimate the complex refractive index of each dust sample. Our results show that the magnitude and spectral dependence of the dust extinction and refractive indices differ according to particle mineralogy, suggesting the necessity for regionally resolved optical properties for modeling dust radiative effects in the longwave. The magnitude of extinction is controlled by the particle size distribution and remains significant down to low coarse particle concentrations, indicating that the longwave effect of mineral dust persists throughout long‐range transport and is thus relevant at the global scale.